STRUCTURAL CHARACTERIZATION OF PLATINUM DEPOSITS SUPPORTED ON ORDERED ALUMINA FILMS - Libuda, Jörg; et al. (Journal of Vacuum Science & Technology A, 1994)
Platinum on gamma-Al2O3 represents one of die technically important supported catalysts. In order to model such a system, we have prepared a well-ordered 5-angstrom-thick and atomically flat oxide film with gamma-alumina-like structure on NiAl(110). Its defect structure has been subject to a spot-profile analysis-low-energy electron diffraction (SPA-LEED) investigation. The formation of antiphase domains leads to a broadening or splitting of certain superstructure spots, which exhibit unusual intensity up to high diffraction orders. The deposition of small amounts of platinum results in destruction of the oxide superstructure to a great extent. This behavior allows the investigation of small platinum coverages (theta almost-equal-to 0.1). Island sizes and further information about size distributions were extracted from a spot-profile analysis of the (00)-LEED reflex, revealing a high dispersion of platinum with Pt atoms changing die structure of the oxide in their immediate neighborhood. Thermal desorption spectroscopy results suggest an embedding of Pt in the Al2O3 matrix. To a large extent this process can be suppressed by deposition at low temperature (100 K), whereas heating higher than 800 K leads to diffusion of Pt through the oxide into the substate followed by a recovering of the oxide superstructure. Deposition of several monolayers of platinum at 500 K results in the formation of a polycrystalline film. The crystallites grow in (111)-orientation and show preferential azimuthal orientations with respect to the substrate.